Kajian Literasi Kewirausahaan terhadap Rumah Tangga Keluarga Pelaku Industri Sagu - Mitra Amalia Gama; Muhammad Hasan; Nurdiana Nurdiana; Inanna Inanna; Muhammad Ihsan Said (Indonesian Journal of Social and Educational Studies, 2021)
Abstract. This research was conducted with the aim of knowing the level of understanding of entrepreneurial literacy in Redo Village, Larompong District, Luwu Regency and to determine the potential utilization of the area in Redo Village, Larompong District, Luwu Regency as a place for the sago making industry.The type of research used is descriptive qualitative. Data collection methods are through observation, interviews, and documentation. The data analysis design used in this study is a qualitative descriptive analysis that takes place from the first time you enter the field to collect data and answer a number of existing problems, then proceed by writing, editing, classifying and the presentation stage.The results showed that the presence of entrepreneurial literacy can add new ideas for business actors, MSMEs, because it can help find new innovations and new ideas and can produce quality, superior, innovative resources and can determine business actors and employees. Keywords: Entrepreneurial Literacy, Households of Sago Industry Actors, MSMEs,Home industry, Enterpreneurship